Meningkatkan Hasil Belajar Matematika Materi Bilangan Bulat Melalui Pendekatan Kontekstual Pada Siswa Kelas VII MTsN 1 Probolinggo - Sindi Aulia; Moh Syadidul Itqon; Nurul Isnaini (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This classroom action research (CAR) aims to improve mathematics achievement in integers in seventh grade students of MTsN 1 Probolinggo through the application of the Contextual Teaching and Learning (CTL) approach, and to describe students' responses to the application of this approach. The contextual approach emphasizes learning through 'experience' rather than 'memorization' and connects learned concepts to the real world. This study uses the Kemmis and Taggart spiral model of CLAR, which consists of two cycles. The subjects of the study were seventh grade students of MTsN 1 Probolinggo in the 2025/2026 academic year. The results of Cycle I showed an average formative test score of 175.86 with a classical completion percentage of 51.72% (15 out of 29 students completed the test), which did not meet the classical success indicators (e.g., 85%). After improvements in Cycle II, the average formative test score increased to 104.83, with 27 students completing the test, so that the classical completion percentage reached 93.10%. This significant improvement demonstrates that the implementation of contextual learning strategies is effective in improving mathematics learning outcomes and meeting classical completeness standards.